Map location and nucleotide sequence of korA, a key regulatory gene of promiscuous plasmid RK2. - Bechhofer, D H (1983)
From our earlier work, we know that the korA gene of broad host range plasmid RK2 is located within the 50.4'-56.4' region. By additional subcloning of this region, we have mapped korA to the segment between the HaeII site at 55.0' and the HincII site at 55.6'. The direction of korA transcription (55.6' to 55.1') was determined by two methods: (1) inactivation of korA expression signals and fusion of the structural gene to other promoters; and (2) hybridization analysis of korA-specific RNA's synthesized in vivo. We have determined the nucleotide sequence of the korA region. A potentially strong promoter overlaps the HincII site at 55.6', and there is a coding region which specifies the putative korA polypeptide. That this is the korA gene was supported by sequence analysis of Ba131-generated deletion mutants of korA. The sequence shows the korA product to be a small, basic polypeptide of 101 amino acids.